Analisis Kebijakan Keamanan Nasional Indonesia Ditinjau Dari Kelembagaan dan Perkembangan Ancaman - Nour Zattullah; Ichsan Malik; Eri Radityawara Hidayat (Universitas Batanghari Jambi, 2022)
Defense and security are two concepts that cannot be separated from the life of the nation and state. After Reformasi Era, the concepts of defense and security in Indonesia were absolutely separated, which was also followed by the separation of the TNI and POLRI, previously known as ABRI. This study analyzes the relevance of national security policies in Indonesia, which separates the concepts of defense and security, compared to the latest developments in threats to Indonesia's existence as a country. This study uses a qualitative method. This study finds that the complexity of the threats that come to the existence of the Indonesian state and the security of its people has developed into a multi-spectrum and cross-sectoral, so that cross-sectoral resources are needed for handling it. Referring to the Sishanta doctrine adopted by Indonesia, the handling of threats should be able to empower all resources owned by the components of the nation, not dichotomizing threats, and handling them comprehensively through good interagency. The plan to form a National Security Council is important to fill this gap, where this council is expected to be a forum for the final assessment of emerging threats to further direct state institutions in synergizing with one another, empowering their resources in handling threats.